Reconstructing the Concept of Hadith on Niyyah (Intention) toward the Essential Roles of Religious Teachers and Students in the Digital Era - Diniputri Azhari; Abdul Azis Teo; Hanum Lestari Ningsih; Apriliah Liah (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2026)
ENGLISH: Reconstructing the Concept of Hadith on Intention toward the Essential Roles of Religious Teachers and Students in the Digital EraObjective: This study aims to reconstruct the concept of intention (niyyah) in the Prophetic traditions as a conceptual foundation for the essential roles of Islamic education teachers and students in addressing the challenges of the digital era. Method: A qualitative approach using content analysis was employed to examine relevant hadith, classical hadith commentaries, cognitive psychology literature, and studies on Islamic and digital education. Results: The findings indicate that intention functions not only as a prerequisite for worship but also as a pedagogical foundation that fosters self-awareness, self-regulation, digital integrity, academic honesty, a culture of tabayyun (critical verification), and the ethical use of technology as a wasilah to achieve the ultimate educational purpose (ghayah). Conclusion: The reconstructed concept of intention provides an ethical framework integrating digital competence with spiritual and moral values in Islamic education. Contribution: This study proposes a novel conceptual model integrating Prophetic traditions, cognitive psychology, and digital education to strengthen the digital integrity of Islamic education teachers and students through value-based educational practices.INDONESIAN: Rekontruksi Konsep Hadis Niat terhadap Esensi pada Peran Guru Agama dan Siswa di Era DigitalTujuan: Penelitian ini bertujuan merekonstruksi konsep hadis tentang niat sebagai landasan konseptual bagi esensi peran guru agama dan siswa dalam menghadapi tantangan pendidikan di era digital. Metode: Penelitian menggunakan pendekatan kualitatif dengan metode content analysis terhadap hadis tentang niat, kitab syarah hadis, literatur psikologi kognitif, serta kajian pendidikan Islam dan pendidikan digital. Hasil: Temuan menunjukkan bahwa niat tidak hanya berfungsi sebagai syarat sah ibadah, tetapi juga sebagai landasan pedagogis yang membentuk self-awareness, self-regulation, integritas digital, kejujuran akademik, budaya tabayyun, dan pemanfaatan teknologi sebagai wasilah untuk mencapai tujuan pendidikan (ghayah). Kesimpulan: Rekonstruksi konsep niat menghasilkan kerangka etis yang mengintegrasikan kompetensi digital dengan nilai spiritual dan moral. Kontribusi: Penelitian ini menawarkan model konseptual baru yang mengintegrasikan hadis, psikologi kognitif, dan pendidikan digital sebagai paradigma pendidikan Islam berbasis nilai untuk memperkuat integritas guru agama dan karakter siswa pada era transformasi digital.